Implicaciones filosóficas de algunos recientes descubrimientos en torno al origen y a la naturaleza del lenguaje - Galparsoro, José Ignacio (Revista de Filosofía, 2007)
As opposed to Descartes, and in accordance with authors such as Nietzsche, Darwin or Chomsky, Pinker sustains that language is just another instinct of human nature. But he differs himself from Chomsky by affirming that language is also the result of the mechanism of natural selection. Recent discoveries seem to strengthen Pinker’s thesis, in as far as it has been possible to establish a link between the FOXP2 gene and language. Philosophy should take good note of these results, as they fully affect the status of lógos: from now on, it is possible, without needing to resort to any type of transcendence, to consider language as constitutive of human singularity regarding other species and, at the same times, as just another avatar in the evolution of the natural world.